Conventional Boundaries of Professionalism in Contemporary Social Work: A Theory-to-Practice Gap - Wilson, Courtney (Université d'Ottawa | University of Ottawa, 2020)
All professions are governed by established boundaries to address inherent power imbalances between the professional and the individual accessing services. In the field of social work, the advocated boundaries of professionalism are restrictive, defensive and protective in nature; they serve to separate the service provider and the service user, and to distinguish appropriate and inappropriate behaviour on the part of the service provider. This dissertation offers a meta-analysis of relevant literature pertaining to professional boundaries in the context of social work, paired with findings that are supported by the author’s autoethnographic experiences. Ultimately, the results demonstrate how the boundaries of professionalism in the context of social work can contradict the values and principles of contemporary practice, can be too rigid and unsuited to the situation or context, or can be too blurred and thus generate confusion and discomfort among social workers. Chaque profession est régie par des limites établies afin de remédier aux déséquilibres de pouvoir inhérents à la relation entre le professionnel et l'individu qui accède aux services. Dans le domaine du travail social, les limites du professionnalisme préconisées sont restrictives, défensives et protectrices ; elles servent à séparer le prestataire de services et l'utilisateur de services, et à distinguer les comportements appropriés et inappropriés de la part du prestataire de services. Ce mémoire propose une méta-analyse de la littérature pertinente concernant les limites professionnelles dans le contexte du travail social, associée à des résultats qui sont soutenus par les expériences autoethnographiques de l'auteure. En fin de compte, les résultats montrent comment les limites du professionnalisme dans le contexte du travail social peuvent être en contradiction avec les valeurs et les principes de la pratique contemporaine, peuvent être trop rigides et inadaptées à la situation ou au contexte, ou peuvent être trop floues et peuvent ainsi générer de la confusion et de l'inconfort chez les travailleurs sociaux.